Modifikasi Alat Pengasapan Ikan Rumahan Sistem Tertutup - Sindy Nindia Maretha Haristanti; Kelvin Febrianto; Suyanto Suyanto; Dhela Nanda Oktavia (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to design a closed fish smoking device using coconut fiber as an energy source to smoke cursed fish or snakehead fish, which is different from traditional smoking equipment. This research was carried out in the tool making stage and the tool testing stage. This fish smoking tool modification is designed from an iron, aluminum frame and stainless steel rack. The open process of smoking fish at home has disadvantages such as unknown temperature and smoke, resulting in uneven maturity levels and longer smoking times. The research method was carried out by making tools and testing the tools. The time required for the process of smoking fish using this modified tool is around 50 to 60 minutes with the fuel amount being 2 kg of coconut husks and coconut shells with 150 ml of kerosene. This smoking tool is more efficient in carrying out smoking because the smoke is trapped in the drum tube, there is only one chimney so that the smoke is more easily absorbed by the fish and has a more distinctive characteristic in smoking.